Validasi Metode Analisis Niasinamid dan Asam Kojic Menggunakan Kromatografi Cair Kinerja Tinggi dan Aplikasinya dalam Sediaan Kosmetika: Validasi Metode Analisis Niasinamid dan Asam Kojic Menggunakan Kromatografi Cair Kinerja Tinggi dan Aplikasinya dalam Sediaan Kosmetika - Aqnes Budiarti; Ninda Ariyanti; A Khoirul Anwar (JURNAL FARMASI DAN MAKANAN, 2025)
The combination of niacinamide and kojic acid is widely used in skin lightening cosmetics. Although the combination is effective, the safety was limited by its levels in the preparation. The levels of both are relatively small, so required sensitive and simultaneous analysis methods. This study aims to develop an analysis method of niacinamide and kojic acid and apply validated method to cosmetics. The study used an isocratic type HPLC (Jazco) with UV-Vis detector at 268 nm. The stationary phase was C18 and the optimized mobile phase was acetonitrile: aquabides (20:80, v/v) with flow rate 1.0 mL/min. Validation tests of linearity, accuracy, precision, selectivity, and sensitivity (LOD and LOQ). The results showed that the developed method can be validated and applied. The linearity tests resulted a value of r=0.999; niacinamide accuracy 99.78-100.75% and kojic acid 99.79-100.69%, precision of both produced a %RSD value≤ 2%; The LOD and LOQ of niasinamide 0.026 μg/mL and 0.086 μg/mL; The LOD and LOQ of kojic acid 0.462 μg/mL and 1.540 μg/mL, selectivity was good. The niacinamide content in samples A, B, and C were 0.052%, 0.100%, and 0.138%. The kojic acid content in samples A, B and C were 0.610%; 1.127% and 1.531%, w/w.